Drug Delivery Systems for Phthalocyanines for Photodynamic Therapy - Rak, Jakub; Pouckova, Pavla; Benes, Jiri; Vetvicka, David (Anticancer research, 2019)
The focus of this review is to describe the state-of-art in the development of innovative drug delivery systems for phthalocyanines as photosensitizers for photodynamic therapy (PDT). PDT is a medical treatment combining photosensitizers (PSs) activated by visible light of a specific wavelength to selectively destroy targeted cells, tumor tissues and its surrounding vasculature. In the last decades, PDT has been under intense investigation, first as a promising alternative approach for improved cancer treatment, later against microbial infection and nowadays, mainly in aesthetic medicine, against age-related degeneration. The success of PDT is restricted because of difficulties with administration and skin permeation of PSs. As PDT importance raises, there is high interest for advanced formulations and delivery systems (DDS) for PS, especially formulations based on nanotechnology. Accordingly, this review deals with the innovations pertaining to DDS for PDT as disclosed in recent patents and literature.
Keywords: fotosenzibilizující látky; Indoles; lidé; lékové transportní systémy; indoly; Photochemotherapy; fotochemoterapie; Photosensitizing Agents; Drug Delivery Systems; Humans